Does coworkers' upward mobility affect employees' turnover intention? The roles of perceived employability and prior job similarity. Issue 12 (4th July 2022) - Huang, Weize; Wang, Duanxu; Pi, Xin; Hewlin, Patricia Faison
Abstract: What would employees do if their coworkers move upwardly to other organizations? In the era of boundaryless career, voluntary turnover is more prevalent than ever before. Effects of coworkers' voluntary turnover on employees' turnover are attracting attention in human resource management. However, this stream of research has generated mixed findings showing both positive and negative effects on focal employees' turnover, and scholars still know little about the specific mechanism through which the effects occur. This study takes the first step to reconcile the mixed findings and unfold the black box of the effects. Specifically, we argue that the mobility direction of coworkers' turnover should not be overlooked by previous research, and we propose that coworkers' upward mobility plays an indispensable role in predicting employees' turnover intention. Based on social comparison theory, we hypothesize that coworkers' upward mobility positively relates to focal employees' turnover intention through focal employees' perception of employability. Furthermore, we propose prior job similarity as a contingency that activates the relationship mentioned above, such that the mediation effect is stronger with higher prior job similarity. Our hypotheses were tested and fully supported by two-wave data from a sample of 369 employees in China. Lastly, theoretical and practical implications are discussed along with possible limitations and directions for future turnover research.